The Gruffalo's child - Donaldson, Julia; Scheffler, Axel (London : macMillan, 2004)
The Gruffalo's Child goes out to find the Big Bad Mouse she has heard so much about.
Keywords: Animals -- Juvenile fiction; Curiosity -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme; Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme